VISUALISASI DAN NARASI BUDAYA NUSANTARA DALAM PERSPEKTIF POSKOLONIAL PADA PROGRAM BELAJAR INDONESIA - Utami, Citra Dewi (Institut Seni Indoensia Surakarta, 2010)
Television, both as a phenomenon as well as a cultural agent, is framing the world by means of linguistic codes. This cultural and media studies-based research applies Stuart Hall’s theories of representation and identity by which the Barthesian’s visual semiotics approach and postcolonial perspective as analysis method are used. This research aims at (a) identifying how Indonesian culture has been visualised and narrated. The result of the research confirms several points: hybrid condition bedwen tradisional and modern, the Indonesian culture has been uttering by the narrator.Keywords: postcolonial perspective, visualisation, narative, Indonesian culture